STRUKTUR KOMUNITAS KEPITING DI HUTAN MANGROVE KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG DAN PEMANFAATANNYA SEBAGAI MEDIA PEMBELAJARAN BIOLOGI - Rauf, Abd (JSTT, 2016)
This research aims to know community structure of crabs present in mangrove at Pinotu village, Toribulu subdistrict, Parigi Moutong regency and to developed its resultant for biology learning media being a pocket boo. The research was descriptivelycarried out at the village and was improved to design 4D. Sampling was undertaken by observing crabs found in each of the determinate stations in which those was then divided into quadrant transect and retrieval time consisting of 11.30 – 12.30; 17.00 – 18.00; 23.30 – 24.30 periods. The resultant observation was eventually to be a pocket book for biology learning media. Results of the research showed that 6 species of crabs were found in the area including Uca annulipes, Uca rosea, Uca paradussumieri, Scylla serrata, Epixanthus dentatus, and Sarmatum germaini. Total of the observed crabd was 297 individuals. Absolute density value and retrieval times were mostly found in station II during 18.00 – 19.00 periods. Sarmatium germaini was a species of crabs possessing the highest of the relative density value (55,56%). Moreover, diversity index per station ranged 0.7305 – 0.7491 that means it was less then 1.0 indicating a low diversity. For dominancy index, it ranged 0.678 – 0.776. the highest dominancy was observed in station III valued 0.0776 suggesting that a richness of species of crabs was a quite low. Distribution patterns of species present in station I, III, and III were 0.394, 0.304, and 0.016, respectively, recommending that those were uniform distribution patterns. These seems that the habitats, physical factors, retrieval times strongly affected on crab community present in the mangrove forest. In addition, data analysis showed that the community structure of crabs in mangrove forest at Pinotu village was categorized as a low diversity that it was highly resulted in an ecological pressure. The developed pocket book has been validated by content, media, and design experts providng the following value: 91.4%, 9.71%, 77.33%. it has also been tried out to small group and larged group giving the values; 87.2% and 84.4% respectively. Accordingly, the pocket book can be appropriately used as biology learning media.